Competences of a special educator in pre-school and early school education = Kompetencje pedagoga specjalnego w edukacji przedszkolnej i wczesnoszkolnej - Śliwa, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article deals with issues relating to the competences of support teachers working in kindergartens and grades 1-3 of primary schools. It presents, synthetically the areas related to knowledge and skills and attitudes that should be demonstrated by special educators working with children with an intellectual disability. Moreover, the article also explains which formal qualifications a supporting teacher should have and also, those which a special educator working in educational institutions at the pre-school and early school level should have.
Keywords: teacher competences; special education; student with an intellectual disability; kompetencje nauczycielskie; pedagogika specjalna; uczeń niepełnosprawny intelektualnie